Theological voices in medical ethics - Verhey, Allen; Lammers, Stephen E. (Eerdmans Publ. Company, 1993)
Introduction : Rediscovering religious traditions in medical ethics / Allen Verhey and Stephen E. Lammers -- On Paul Ramsey : A covenant-centered ethic for medicine / David H. Smith -- On James M. Gustafson : Can medical ethics be Christian? / Allen Verhey -- On Stanley Hauerwas : Theology, medical ethics, and the church / Stephen E. Lammers -- On Richard McCormick : Reason and faith in post-Vatican II Catholic ethics / Lisa Sowle Cahill -- On William F. May : Corrected vision for medical ethics / Gilbert Meilaender -- On James F. Childress : Answering that of God in every person / Courtney S. Campbell -- On Germain Grisez : Can Christian ethics give answers? / James G. Hanink -- On Immanuel Jakobovits : Bringing the ancient world to the modern world / Marc A. Gellman -- On Bernard Häring : Construing medical ethics theologically / Ron P. Hamel -- Medical ethics and theology : The accounting of the generations / Martin E. Marty